Assessing the audiotactile Colavita effect in near and rear space. - Occelli, V; O'Brien, J; Spence, C; Zampini, M (2010)
The Colavita effect occurs when participants performing a speeded detection/discrimination task preferentially report the visual component of pairs of audiovisual or visuotactile stimuli. To date, however, researchers have failed to demonstrate an analogous effect for audiotactile stimuli (Hecht and Reiner in Exp Brain Res 193:307-314, 2009). Here, we investigate whether an audiotactile Colavita effect can be demonstrated by manipulating either the physical features of the auditory stimuli presented in frontal (Experiment 1) or rear space (Experiment 3), or the relative and absolute position of auditory and tactile stimuli in frontal (Experiment 2) or rear space (Experiment 3). The participants showed no evidence of responding preferentially to one of the sensory components of the bimodal stimuli when they were presented from a single location in frontal space (Experiment 1). However, a significant audiotactile Colavita effect was demonstrated in Experiments 2 and 3, with participants preferentially reporting the auditory (rather than tactile) stimulus on the bimodal target trials. In Experiment 3, an audiotactile Colavita effect was reported for auditory white noise bursts but not for pure tones and selectively for those stimuli presented from the same (rather than from the opposite) side. Taken together, these results therefore suggest that when a tactile and an auditory stimulus are presented from a single frontal location, participants do not preferentially report one of the two sensory components (Experiment 1). In contrast, when the stimuli are presented from different locations, people preferentially report the auditory component, especially when they are spatially coincident (Experiments 2 and 3). Moreover, for stimuli presented from rear space, the Colavita effect was only observed for auditory stimuli consisting of white noise bursts (but not for pure tones), suggesting that this kind of stimuli are more likely to be bound together with somatosensory stimuli in rear space.